Developing a virtual interdisciplinary research community in higher education. - Richardson B; Cooper N (Journal of Interprofessional Care, 2003)
As multidisciplinary collaboration in both clinical and research settings is becoming a key aspect of contemporary health care, strategies to enhance interprofessional interaction in postgraduate research programmes can offer important experiences to facilitate ongoing interprofessional relationships. This paper provides a retrospective appraisal of a strategy which used computer-mediated communication to develop a virtual community network, known as'health_voice' accessed through a web page. The rationale for developing the network is presented, and the process of designing and establishing the web-site through an action research approach is described The outcome of the strategy is reviewed with regard to the relationships between the real' and 'virtual' community. Reflections on the developmental process contextualise the initiative within a concept of a community-of-practice. It is acknowledged that the use of a virtual arena for communication within a research community involves a cultural change in the dynamics of higher degree teaching and learning. Future plans to further embed the virtual environment within a postgraduate research culture are given.